The Effect Of Persuasive Communication On TIKTOK Live Odeliz.ID Accounts On Increasing Customer Buying Interest: PENGARUH KOMUNIKASI PERSUASIF AKUN TIKTOK LIVE ODELIZ.ID TERHADAP MENINGKATNYA MINAT BELI CUSTOMER - Aditya Dimas Pratama; Sinta Rizki Maulida (MEDIAKOM, 2025)
The rapid development of social media, especially TikTok, which is increasingly used as a platform for product promotion and sales through live streaming features, requires business actors to think more about strategies to increase customer purchase interest, one of which is through persuasive communication. This study aims to determine the effect of persuasive communication on the purchase interest of customers of the TikTok account Odeliz.id.The research method used in this study is quantitative explanatory. Data was obtained through questionnaires distributed to 109 respondents selected using the simple random sampling technique. The measurement tools used in this study are the Persuasive Communication Scale questionnaire (r = 0.85) and the Purchase Interest Scale (r = 0.87). The data analysis technique used is Simple Linear Regression Analysis. The results of the study show that persuasi vecommunication has a significant influence on customer purchase interest (F = 47,876, p < 0,01 ) with a contribution of 31.2%, while 68.8% is influenced by other variables outside this study. Suggestions for future research include exploring other variables that may influence customer purchase interest and expanding the research sample to obtain more comprehensive results. Keyword : persuasive communication, tiktok, customer purchasing interest